Growth and Production of Zea mays on Weed Management and Land Preparation in Three Diffrenet Places in Sumatera Utara - Fitria Fitria (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Loss of corn crop yields due to competition with weeds approximately 40-50%. To overcome the negative impacts, it is necessary to prepare land such as no tilage which is one of the alternatives in the preparation of land for corn crops.